L’héritage conservateur du néolibéralisme - Martin Beddeleem; Nathanaël Colin-Jaeger (Astérion, 2020)
The 1930s and 1940s marked a period of crisis for liberalism. Authors as diverse as Friedrich Hayek, Wilhelm Röpke, Walter Lippmann, Michael Polanyi and Louis Rougier came together at two seminal events, the Walter Lippmann Colloquium in 1938 and the creation of the Mont-Pèlerin Society in 1947, to rethink liberalism. This rethinking of the liberal project prompted them to carry out a diagnosis of the crisis of liberalism, which, for the authors mentioned, dated back to the French Revolution. This article seeks to demonstrate the coherence of the neoliberal project from their historical diagnosis in this period of crisis. Indeed, by criticising the French Revolution and its effects as part of a harmful rationalism, which gave rise to both a laissez-faire approach and various collectivisms, neoliberals explicitly took up concepts from critics of the revolution, especially Edmund Burke. The concept of tradition, understood as covering social and legal rules that have slowly evolved to constitute coordination mechanisms that allow our actions, is thus very widely taken up and valued by neoliberals. We, therefore, interpret neoliberal theory on the basis of this recategorisation of the concept of tradition, and point out the affinities between neoliberal positions and philosophical conservatism. This alignment reveals several conceptual tensions between cultural evolutionism on the one hand and the defence of significant Western values on the other.